‘in situ’ Synthesis of a Trinuclear Nickel(II) Complex with a 40-Membered Macrocyclic Tricompartmental Hexadecaaza Dodecadentate Ligand Using Kinetic Template Reaction - Rai, H.C.; Ghosh, A.K.; Priyanka (Asian Journal of Chemistry, 2010)
A novel nickel(II) complex with the ligand 4,5,24,25-tetramethyl-10,11:18,19:30,31:38,39- tetrabenzo-2,3,6,7,9,13,16,20,22,23,26,27,29,33,36,40-hexadecaazatricyclo-[26,12,0,08,21]- tetraaconta-1,3,5,7, 10,12,16,18,21,23,25,27,30,32,36,38-hexadecaene has been synthesized with kinetic template reaction in which dibromobis(biacetyldihydrazone) nickel(II) is allowed to condense with 13,14-exocyclicdioxo-1,5,8,12-tetraaza-2,3:10,11-dibenzo-cyclotetradeca- 2,4,8,10-tetraenato(2-) nickel(II) in 1:2 molar ratio in DMF medium under nitrogen at 100 ºC. Characterization has been done with elemental analysis, conductivity and magnetic susceptibility measurements, electronic and vibrational spectral studies. The nickel(II) ions are in different stereochemical environments.